A high performance solid state asymmetric supercapacitor device based upon NiCo2O4 nanosheets//MnO2 microspheres. Issue 74 (25th July 2016) - Khalid, Syed; Cao, Chuanbao; Wang, Lin; Zhu, Youqi; Wu, Yu
Abstract : The volumetric energy density and power density of a novel solid state device (NiCo2 O4 //MnO2 ) are much higher than most reported devices. Abstract : A high performance solid state asymmetric supercapacitor (SSASCs) device is successfully fabricated by combining NiCo2 O4 as positive and MnO2 as negative electrode materials. Herein, we also report a facile strategy to synthesize mesoporous layered NiCo2 O4 nanosheets and 3D hierarchical MnO2 microspheres by a simple microwave heating method. Both materials exhibit excellent electrochemical performance due to their unique morphological features along with nanocrystallite size, high specific surface area, narrow pore size distribution and large pore volume. The SSASCs device operates within the potential window of 1.5 V and exhibits high volumetric capacity and energy density of 0.954 mA h cm −3 (2.3 F cm −3 ) and 0.715 mW h cm −3 at 1 mA cm −2 respectively. The device also demonstrates excellent cyclic stability with capacity retention of 83% by the end of 10 000 cycles at a current density of 2 mA cm −2 . This work constitutes the first demonstration of using 3D hierarchical MnO2 microspheres as a high energy negative electrode for a SSASCs device. A SSASCs device with high volumetric capacity and energy density has significant potential applications in portable electronics and electrical vehicles.